Implementation of the Problem-Based Learning Model with Spotlight Techniques in Increasing Motivation for Learning History of Class XI MIPA 6 Students at SMAN 2 Banda Aceh. - Yanti, Ulfa; Fauziah; Nurasiah (Riwayat: Educational Journal of History & Humanities, 2023)
This research aims to look at the implementation of the problem-based learning model with the spotlight technique on the learning motivation of class XI MIPA 6 students at SMAN 2 Banda Aceh. This type of research is Collaborative Classroom Action Research which is carried out synergistically with the teacher in class, to increase student learning motivation. The subjects in this study were students of class XI MIPA 6 which amounted to 23 people. The data collection techniques used were observation and questionnaires. The data obtained were analyzed qualitatively descriptive. Based on the research results, it was found that there was a change in student behavior from the pre-cycle to cycle 1 and cycle 2. This was demonstrated by the questionnaire's pre-cycle results, which had a proportion of 67.60% in the "Enough" category. Cycle 1 was 77.42% and met the "Good" standard. Cycle 2 saw a difference of 81.50% using the "Good" criteria.. The learning process using problem based learning with the spotlight technique is considered very interesting by students because it focuses them on learning and is able to increase their motivation or desire to learn history in themselves.